La Vie métrique de Théodore Stoudite par Stéphane Mélès (BHG 1755m) - Delouis, Olivier (Analecta Bollandiana, 2014)
Abstract The metric Life of Theodore the Studite (759-826, BHG 1755m) was written by Stephanos Meles, who became logothete of the drome during the reign of John II Komnenos (1118-1143). The article includes a new edition of Stephanos’ poem along with an annotated French translation. The Meles family, the author’s cultural background, the text’s literary genre as well as its relationship with a 10th-century prose model (the so-called Life A, BHG 1755) are other issues discussed in the present study.